Technical and economic assessment of process integration in gasoline production - Muhammed, Tasneem (2021)
In chemical engineering, process design is a fundamental attribute that includes process definition, simulation, and optimization. Commonly, superstructure approaches are used for process design. These approaches represent the process by integrating simpler unit blocks described by physical and chemical properties to retrofit complex chemical processes. The superstructure approaches follow certain objectives (e.g. economic, environmental and social) that can be optimized. This makes the implementation of superstructure approaches in process design a challenging task.